Helpbot: multipurpose robot / Uzaini Ahmad … [et al.] - Ahmad, Uzaini; Arman, Muhamad Amar Sufi; Ramli, Mohd Sufian; Abd Wahid, Siti Sufiah; Hasan, Khairul Kamarudin (Division of Research and Industry Linkages, 2017)
The aim for this project is to move an item from one place to another by using mobile hand robot. The body of this robot comprises of servo motors, DC motors and Arduino microcontroller board. Moreover, the control signal is manual input and sent via Bluetooth communication to make the robot following the desired movement. This robot can be served as a safety measurement for the researches when handling and experimenting hazard chemicals. The robots tend to possess some or all of the following abilities and functions: accept electronic programming, process data or physical perceptions electronically, operate autonomously to some degree, move around, operate physical parts of itself or physical processes, sense and manipulate their environment, and exhibit intelligent behavior especially behavior which mimics humans or other animals.